2003
DOI: 10.1002/chin.200304154
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Activity of 1‐ and 10‐N‐Substituted 1(10),2,3,4‐Tetrahydropyrimido[1,2‐a]benzimidazoles.

Abstract: Fused pyrimidine derivativesFused pyrimidine derivatives R 0515 Synthesis and Pharmacological Activity of 1-and 10-N-Substituted 1(10),2,3,4-Tetrahydropyrimido[1,2-a]benzimidazoles. -A variety of new N-substituted pyrimidobenzimidazoles [cf. (V), (VIII), (X)] are synthesized and screened for their pharmacological properties. Some derivatives possess spasmolytic, anti-aggregating and/or hypotensive activity. -(ANISIMOVA, V. A.; OSIPOVA, M. M.; SPASOV, A. A.; TURCHAEVA, A. F.; DUDCHENKO, G. P.; LARIONOV, N. P.; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…It has been suggested that hyperinsulinemia may have increase free radicals and therefore promote aging, independent of glycemia [39,77,78,151,152]. Plasma levels of lipid hydroperoxides are higher, and antioxidant factors are lower in individuals who are resistant to insulin-stimulated glucose disposal but otherwise glucose tolerant, nonobese, and normotensive [77].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that hyperinsulinemia may have increase free radicals and therefore promote aging, independent of glycemia [39,77,78,151,152]. Plasma levels of lipid hydroperoxides are higher, and antioxidant factors are lower in individuals who are resistant to insulin-stimulated glucose disposal but otherwise glucose tolerant, nonobese, and normotensive [77].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 27 new compounds were synthesized as described previously [6] , [7] , [8] , [9] , [10] , [11] and tested for IOP lowering effect in ocular normotensive rats. These compounds included twenty 9H-imidazo[1,2-a]benzimidazoles, four 10H-pyrimido[1,2-a]benzimidazoles, two 1H-pyrimido[1,2-a]benzimidazoles and one 1H-imidazo[1,2-a]benzimidazole.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Benzimidazoles are heterocyclic compounds that are known for numerous therapeutic effects and are recognized as important pharmacophore in drug discovery [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . Over the past years, several benzimidazole derivatives have been synthesized and their pharmacological activities investigated.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations